2013
DOI: 10.1021/bi4000832
|View full text |Cite
|
Sign up to set email alerts
|

Peroxide-Shunt Substrate-Specificity for the Salmonella typhimurium O2-Dependent tRNA Modifying Monooxygenase (MiaE)

Abstract: Post-transcriptional modifications of tRNA are made to structurally diversify tRNA. These modifications alter noncovalent interactions within the ribosomal machinery, resulting in phenotypic changes related to cell metabolism, growth, and virulence. MiaE is a carboxylate bridged, nonheme diiron monooxygenase, which catalyzes the O2-dependent hydroxylation of a hypermodified-tRNA nucleoside at position 37 (2-methylthio-N(6)-isopentenyl-adenosine(37)-tRNA) [designated ms(2)i(6)A37]. In this work, recombinant Mia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 82 publications
3
30
2
Order By: Relevance
“…It is generally accepted that tRNA 2MeSiPR monooxygenase (MiaE), the only enzyme known to hydroxylate tRNA-bound iP, synthesizes 2MeScZRMP and cZRMP [ 10 , 51 , 61 ]. Yet, trans -selective hydroxylation of tRNA-bound iPR or 2MeSiPR by the same enzyme was reported by others [ 62 , 63 ]. The origin of zeatins in the tRNA of some organisms is entirely unclear, as the presence of the miaE gene is reportedly limited to a few bacterial genera [ 64 ]; however, up-to-date results of BLASTp searches (not shown) using MiaE from Pseudomonas putida [ 65 ] as a query suggests the far wider distribution of MiaE among bacteria than previously anticipated.…”
Section: Formation Of Trans -Zeatin: Unclarified Pathwayssupporting
confidence: 69%
“…It is generally accepted that tRNA 2MeSiPR monooxygenase (MiaE), the only enzyme known to hydroxylate tRNA-bound iP, synthesizes 2MeScZRMP and cZRMP [ 10 , 51 , 61 ]. Yet, trans -selective hydroxylation of tRNA-bound iPR or 2MeSiPR by the same enzyme was reported by others [ 62 , 63 ]. The origin of zeatins in the tRNA of some organisms is entirely unclear, as the presence of the miaE gene is reportedly limited to a few bacterial genera [ 64 ]; however, up-to-date results of BLASTp searches (not shown) using MiaE from Pseudomonas putida [ 65 ] as a query suggests the far wider distribution of MiaE among bacteria than previously anticipated.…”
Section: Formation Of Trans -Zeatin: Unclarified Pathwayssupporting
confidence: 69%
“…This is twice the expected 24 kDa mass for a single copy of the protein, indicating that Pp-MiaE forms a stable homodimer (α 2 ) in solution (SI, Supplementary Figure S2–2 ). Although this dimeric α 2 configuration of Pp-MiaE is the most commonly observed quaternary structures among the non-heme diiron enzymes family, this result is surprisingly in stark contrast of that reported for the monomeric MiaE from S. typhimurium ( 27 , 28 ). Early bioinformatic sequences analyses of enzymes involved in the biosynthesis pathway of ms 2 io 6 A 37 revealed that MiaE proteins clusters mainly into two groups ( 31 ).…”
Section: Resultscontrasting
confidence: 78%
“…The absorption spectrum of as-isolated Pp-MiaE reveals, in addition to the band at 280 nm corresponding to protein absorption, two distinct bands at 320 and 370 nm (Figure 2A ). This is typical of oxygen-bridged dinuclear non-heme iron systems and are attributable to an oxo-to-Fe III charge transfer transition as observed for MiaE from S. thyhimurium ( 27 , 28 ) and other proteins containing μ-oxo-bridged diiron clusters, including ribonucleotide reductase (RNR) and stearoyl-ACP desaturase (Δ 9 D) ( 42 , 57 ). Similarity to these enzymes is further supported by EPR spectroscopy.…”
Section: Resultsmentioning
confidence: 76%
“…Verification of enzymatic product was performed by multiple reaction monitoring (MRM) using a triple quadrupole LC-MS/MS [Shimadzu Scientific Instruments, LCMS 8040] [3436]. For each experiment, 10 μL of the benzothiazole standard ( described above ) was injected to determine the product ions and relative distribution for each ion.…”
Section: Methodsmentioning
confidence: 99%